2017
DOI: 10.1021/acs.iecr.7b01920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcination Temperature on Morphology, Microstructure, and Photocatalytic Performance of TiO2 Mesocrystals

Abstract: We synthesized TiO2 mesocrystals using a hydrothermal method and investigated the effect of calcination temperature (100–800 °C) on their morphology, crystallinity, and photocatalytic activity. While no appreciable changes in the shape, dimension, and crystal structure of the TiO2 nanoparticles (NPs) were observed as the calcination temperature increased to 300 °C, the crystallinity improved with increasing temperature. The mesocrystal form of the NPs began to disappear at 400 °C, and the specific surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…P25-TiO 2 has surface area of 40 m 2 /g. Calcination at a high temperature led to the reduction of surface area and increased rutile component [23]. However, changing calcination atmosphere from air to H 2 and N 2 did not change the BET surface area.…”
Section: Characteristics Of the P25-tio 2 Catalystsmentioning
confidence: 90%
“…P25-TiO 2 has surface area of 40 m 2 /g. Calcination at a high temperature led to the reduction of surface area and increased rutile component [23]. However, changing calcination atmosphere from air to H 2 and N 2 did not change the BET surface area.…”
Section: Characteristics Of the P25-tio 2 Catalystsmentioning
confidence: 90%
“…Among the existing mesocrystal photocatalysts, the development of TiO 2 mesocrystals has been attracting increased attention; therefore, the appearance and morphology details of TiO 2 mesocrystals are abundantly available as compared to others, including ellipsoidals, spheres, polyhedra, nanosheets, and nanorods. [35][36][37][38][39][40][41][42][43][46][47][48][49][52][53][54][55][56][57][58][59]61,65 In this subsection, we initially summarize the synthesis strategies of the different abovementioned species. Thereaer, versatile applications in photocatalytic hydrogen evolution and organics degradation, as well as the corresponding structure-related photocatalytic mechanisms, are discussed by using typical examples.…”
Section: Mesocrystal Photocatalystsmentioning
confidence: 99%
“…Based on earlier literature, [44][45][46][47][48] it is found that spindle-shaped anatase TiO 2 mesocrystals can be facilely synthesized on a large scale through mesoscale assembly in titanium salt/acetic acid systems without any additives under solvothermal conditions. The acetic acid and solvothermal conditions are the key factors for the synthesis of spindle-shaped TiO 2 mesocrystals, whereas the type of titanium salt is adjustable, including tetrabutyl titanate, 44,45 butyl titanate, 46 titanium butoxide, 47 and titanium tetrachloride. 48 For example, Qi and coworkers have demonstrated the rst additive-free synthesis of porous anatase TiO 2 mesocrystals with a single-crystal-like SAED pattern by using tetrabutyl titanate as the titanium source and acetic acid as the solvent.…”
Section: Photodegradation Of Methylene Bluementioning
confidence: 99%
See 1 more Smart Citation
“…The calcinations influence the reusability and hydrogenation capability of catalyst [213]. Zhang et al investigated phenol degradation through the different calcined catalyst.…”
Section: Effect Of Calcinationsmentioning
confidence: 99%